The effect of audit opinion, financial distress, and good corporate governance on audit delay - Sugiyanto Sugiyanto (Keberlanjutan)
This research examines the effect of financial distress, audit opinion, and good corporate governance on audit delays in Indonesian mining sector companies. By using panel data regression analysis, this study found that financial distress positively affects audit delay. Meanwhile, audit opinions and GCG are not proven to affect audit delay.